Recent Advances in Meningioma Immunogenetics - Al-Rashed, May; Foshay, Kara; Abedalthagafi, Malak (Frontiers in Oncology, 2020)
Meningiomas are relatively common, and typically benign intracranial tumors, which in many cases can be cured by surgical resection. However, less prevalent, high grade meningiomas, grow quickly and recur frequently despite treatment, leading to poor patient outcomes. Across tumor grades, subjective guidelines for histological analysis can preclude accurate diagnosis, and an insufficient understanding of recurrence risk can cloud the choice of optimal treatment. Improved diagnostic and prognostic markers capable of discerning between the 15 heterogeneous WHO recognized meningioma subtypes are necessary to improve disease management and identify new targeted drug treatments. In this review, we show the advances in molecular profiling and immunophenotyping of meningiomas, which may lead to the development of new personalized therapeutic strategies.